2018
DOI: 10.1371/journal.pone.0199023
|View full text |Cite
|
Sign up to set email alerts
|

Clinical use of submaximal treadmill exercise testing and assessments of cardiac biomarkers NT-proBNP and cTnI in dogs with presymptomatic mitral regurgitation

Abstract: Exercise intolerance is the first symptom of heart disease. Yet an objective and standardised method in canine cardiology to assess exercise capacity in a clinical setting is lacking. In contrast, exercise testing is a powerful diagnostic tool in humans, providing valuable information on prognosis and impact of therapeutic intervention. To investigate whether an exercise test reveals differences between dogs with early stage mitral regurgitation (MR) and dogs without cardiac disease, 12 healthy beagles (health… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
31
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 16 publications
(37 citation statements)
references
References 62 publications
2
31
0
Order By: Relevance
“…It is a useful tool to monitor cardiovascular fitness and to prevent overtraining and postexercise fatigue [34,35]. In a Divide R1 W1 R2 W2 R3 W3 R4 W4 R5 Duration of exercise 1 Sec 240 180 300 180 300 180 300 180 240 2,100 Grade 0 1 0 2 0 3 0 4 [22] and to determine cardiac output and maximal oxygen consumption levels, which are the typical indicators of aerobic capacity [36]. In the present study, HR was used as an indicator to verify the primary effect of continuous and interval exercise programs in Beagles.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…It is a useful tool to monitor cardiovascular fitness and to prevent overtraining and postexercise fatigue [34,35]. In a Divide R1 W1 R2 W2 R3 W3 R4 W4 R5 Duration of exercise 1 Sec 240 180 300 180 300 180 300 180 240 2,100 Grade 0 1 0 2 0 3 0 4 [22] and to determine cardiac output and maximal oxygen consumption levels, which are the typical indicators of aerobic capacity [36]. In the present study, HR was used as an indicator to verify the primary effect of continuous and interval exercise programs in Beagles.…”
Section: Discussionmentioning
confidence: 99%
“…In dogs, exercise can cause changes in many physiological parameters. In the studies using Labrador retrievers and Beagles, the incremental treadmill exercise-induced changes in the acute blood lactate, heart rate (HR) [22], and body temperature were reported [23]. Additionally, low-to-high intensity (6% to 20% slope) treadmill exercise considerably affected the physiologic regulators (i.e., cortisol, glucose, and norepinephrine) of both the peripheral and central neuroendocrine systems [24].…”
Section: Introductionmentioning
confidence: 99%
“…In humans and canines, it is released into the circulation four to twelve hours after acute damage [9, 12, 13]. cTnI is not increased in all individuals with mild to moderate DMVD [3, 14].…”
Section: Introductionmentioning
confidence: 99%
“…In a recent study in which different parameters (cardiac biomarkers NT-proBNP and cTnI, heart rate, lactate, acid-base-status, respiratory frequency, blood gases, echocardiography) were measured in combination with exercise testing in dogs, cardiac biomarkers showed the most reliable results [14]. Therefore, exercise in a standardised submaximal treadmill test (SSET) induces different changes in cardiac biomarkers in healthy dogs and in those animals with asymptomatic DMVD.…”
Section: Introductionmentioning
confidence: 99%
“…cTnI is a myocardial intracellular protein that is released by damaged and destroyed cardiomyocytes, resulting in greatly elevated concentrations in the blood [32]. Increased levels of cTnI have been reported in dogs with mitral insufficiency [27], filariasis [3], atrioventricular block [29], cardiac hemangiosarcoma [22], and administration of doxorubicin [25]. Therefore, it has been concluded that a high cTnI concentration in the blood is not only caused by infarct necrosis of the cardiomyocytes, but also by a variety of heart lesions that induce myocardial injury [11].…”
Section: Discussionmentioning
confidence: 99%